Pengaruh Rasa Memiliki, Spiritualitas Dan Pendampingan Pastoral Terhadap Keterlibatan Dalam Pelayanan GMAHK Di Batam - Sandy Hasudungan Tambunan; Stimson Hutagalung; Rolyana Ferinia (Sekolah Tinggi Teologi Berita Hidup, 2023)
The goal of this research is to describe, first, the sense of ownership variable affects involvement in service. The second is the influence of the spirituality variable on involvement in service. The third is the effect of pastoral care on involvement in ministry. Fourth, whether the variables of belonging, spirituality and pastoral assistance have an influence on involvement in service. This study uses a stratified random sampling technique with 110 correspondent the Seventh Day Adventist congregation in Batam. The data that was successfully filtered through the validity test and the classical assumption test were processed to make the regression analysis equation as follows: Y = 0.249 X1 + 0.135 X2 + 0.132 X3 + 10.866. Where variable Y is involvement in ministry, variable X1 is sense of belonging, variable X2 is spirituality, and variable X3 is pastoral care. Hypothesis testing using the t-test proves that separately and simultaneously the sense of belonging, spirituality and pastoral care that have been studied have an effect on the involvement of church members in ministry. Hypothesis testing using the F test also proves that the variables of belonging, spirituality and pastoral assistance to the service involvement variable are 46.8%, and the rest there are other factors that influence 53.2% which were not examined. Keywords: Sense of belonging, Spirituality, Pastoral care, Church minister